Fluorinated surfactants: A review on recent progress on synthesis and oilfield applications - Hussain, Syed Muhammad Shakil; Adewunmi, Ahmad A.; Mahboob, Ahmad; Murtaza, Mobeen; Zhou, Xianmin; Kamal, Muhammad Shahzad (Advances in colloid and interface science, 2022)
The selection of appropriate chemicals and the synthetic method plays an important role in oilfield application. The objectives of this study are to describe the various synthetic route for the preparation of fluorinated surfactants and highlight their oilfield applications. Fluorinated surfactants are the type of surfactants where the hydrophobic tail is either partially fluorinated or replaced totally with fluorine molecules. Fluorinated surfactants have distinct properties compared to corresponding hydrocarbon surfactants such as lower surface tension, better efficiency in lowering the interfacial tension, both oleophobic and hydrophobic nature, high thermal stability, and better chemical tolerance. These properties make them a material of choice for several applications which include but are not limited to fire-fighting, household items, foaming, coating, and paints. Despite these attractive properties, environmental concerns associated with fluorinated surfactants is a major hurdle in extending the application of such surfactants. This review discusses the various synthetic routes for the synthesis of different classes of surfactants such as cationic, anionic, non-ionic, and zwitterionic surfactants. The fundamental surface/interface properties of the synthesized surfactants are also highlighted. In addition, the review highlights the application of fluorinated surfactants in the oil & gas industry. [Display omitted] •Review on fluorinated surfactants•Synthetic routes and methodologies of fluorinated surfactants are discussed.•Oilfield Applications of fluorinated surfactants are reviewed.•Synthetic methodologies focussing on environment friendly fluorinated surfactants